Writing Narrative Essays Using the Problem-Based Learning Model Assisted by Series Drawings in Elementary Schools - Aprima Vista; Elfia Sukma (Jurnal Penelitian Pendidikan IPA, 2023)
Students' low ability to write narrative essays is caused by several problems in the learning process. These problems include teachers not using appropriate learning models in implementing learning. Teachers also do not use appropriate learning media. Apart from that, learning is still teacher-centered which causes students to be less actively involved in learning. This research aims to improve students' ability to write narrative essays using the Problem-Based Learning (PBL) model assisted by a series of pictures. This research is Classroom Action Research (CAR) involving 18 elementary school students. The approach used in this research is a mixed method approach or a qualitative and quantitative approach. The research was carried out in 2 cycles with data collection techniques in the form of document analysis, observation, and tests. The results of the research showed an increase in: a) assessment of teaching modules in cycle I 82.14% (Good) to 92.85% (Very Good) in cycle II, b) observations on the teacher aspect of cycle I 75% (Good) to 85% (Good) in cycle II, while implementation in the student aspect of cycle I was 75% (Good) to 85% (Very Good) in cycle II, c) the assessment of students in cycle I obtained an average of 69.10 and cycle II with an average of 80.10. Based on the research results, it shows that there has been an increase in students' writing skills using the Problem-Based Learning (PBL) model assisted by a series of images.